Mobility of major and trace elements in the eclogite-fluid system and element fluxes upon slab dehydration. (1st February 2017) - Tsay, Alexandra; Zajacz, Zoltan; Ulmer, Peter; Sanchez-Valle, Carmen
Abstract: The equilibrium between aqueous fluids and allanite-bearing eclogite has been investigated to constrain the effect of temperature ( T ) and fluid composition on the stability of allanite and on the mobility of major and trace elements during the dehydration of eclogites. The experiments were performed at 590–800 °C and 2.4–2.6 GPa, and fluids were sampled as synthetic fluid inclusions in quartz using an improved entrapment technique. The concentrations and bulk partition coefficients were determined for a range of major (Mg, Ca, Na, Fe, Al, Ti) and 16 trace elements as a function of T and fluid composition. The results reveal a significant effect of T on element partitioning between the fluids and the solid mineral assemblage. The partition coefficients increase by more than an order of magnitude for most of the major and trace elements, and several orders of magnitude for light rare-earth elements (LREE) from 590 to 800 °C. The addition of various ligand species into the fluid at 700 °C results in distinctive trends on element partitioning. The concentrations and corresponding partition coefficients of most of the elements are enhanced upon addition of NaF to the fluid. In contrast, NaCl displays a nearly opposite effect by suppressing the solubilities of major elements and consequently affecting the mobility of trace elements that form stable complexes with alkali-(alumino)-silicate clusters in the fluid, e.g. high field strength elements (HFSE). The results further suggest that fluids in equilibrium with orthopyroxene and/or diopsidic clinopyroxene are peralkaline (ASI ∼0.1–0.7), whereas fluids in equilibrium with omphacitic pyroxene are more peraluminous (ASI ∼1.15). Therefore, natural aqueous fluids in equilibrium with eclogite at about 90 km depth will be slightly peraluminous in composition. Another important finding of this study is the relatively high capacity of aqueous fluids to mobilize LREE, which may be even higher than that of hydrous melts.